PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM TENTANG GAYA DAN FUNGSINYA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH - Yayan Rahmayantia (Universitas Pakuan, 2019)
IMPROVEMENT OF STUDENT LEARNING OUTCOMES IN NATURAL SCIENCE LESSONS LEARNING ABOUT THE FORCE AND FUNCTION BY USING THE LEARNING MODEL COOPERATIVE TYPE MAKE A MATCHThis study aims (1) To find out the Make a Match type of cooperative learning model can improve student learning outcomes in Natural Sciences about the force and function in class V SD Negeri Bantarjati 7, Bogor Utara, Bogor, semester 2 (2) describe the process of improving student learning outcomes in Natural Science subjects about their force and function before and after using the Make a Match type cooperative learning model in class V SD Negeri Bantarjati 7 (3) To measure the magnitude of the increase in student learning outcomes in Nature Science subjects about force and function after using the Make a Match cooperative learning model in class V of SD Negeri Bantarjati 7. The results of this study indicate that using the Make a Match cooperative learning model can be a fun variation of learning for students so that proven, men increase student learning outcomes in Class V Bantarjati State Elementary School 7. Before using the Make a Match type of cooperative learning model the learning outcomes of students only reached an average value of 62.25 then an increase occurred after using the Make a Match type cooperative learning model to 74, 12 in cycle 1 and 79.125 in cycle 2. From the description above the researchers concluded that the use of a Make a Match type of cooperative learning model adapted to learning material can create a pleasant learning situation so that an increase in student learning outcomes. Therefore the researchers suggest that the use of the Make a Match type of cooperative learning model be socialized and used as an alternative in science learning in schools within the Bogor City Education Office.